Theoretical framework of criteria and indicators for interpreting image and identity in architecture / Linda Shafarina Hassan, Yahaya Ahmad and Fadhillah Nasir. - Hassan, Linda Shafarina; Ahmad, Yahaya; Nasir, Fadhillah (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
Architecture has a significant role in the image and identity of cultural heritage, as it generates outstanding cultural values for a sustainable culture and its context. Meanwhile, contemporary architecture is the most potent agent to the missing local culture of a place. This is due to architecture trends have been rapidly increasing in worldwide and has transforms the image of cultural context into a global city. This scenario shall cause heritage risk when current redevelopment planning scheme has not provided the guaranteed in sustaining cultural image and identity in the new development of cultural context. To sustain the cultural values, it is important to establish criteria and indicators to guide and recommend preservation and incorporation of vital traditional features into new architecture images. This paper uses a critical literature review of previous studies to identify correlated items of image and identity indicators for the development of a new image and identity assessment framework. These indicators reflect the elements and features of the Traditional Malay House (TMH) which has been accepted as the most substantial image and identity character in the context of Kampong Bharu in Kuala Lumpur. Established under the Malay Reserve Enactment 1913 and the Land Enactment 1987, Kampong Bharu represents a significant heritage context in the city, and its cultural identity should be integrated into its new redevelopment strategy and plan. Content analysis of the literature has ascertained 2 general criteria and 55 indicators that are recommended for interpreting image and identity of the Traditional Malay House (TMH).